DEVELOPING A MODULE OF ALPHABET CREATION (MoKHA) AS TEACHINGMEDIA TO INTRODUCE ALPHABETS TO CHILDRENWITH MILD MENTAL RETARDATION - Nurhidayah .; Alan Tri Anafi; Desti Ariany Putri; Noorita Dwi S. (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
The purpose of this study was to produce a product in the form of modules asinstructional media to recognize alphabets for grade 1 students wtih mild mental retardationin Elementary School for Children with special needs in Mardi Mulyo, Tirtomulyo,Kretek, Bantul. The name of the module was Module Creator Alphabet Letters(MoKHA).The method used in this study was Research and Development. The procedureused in the development of this module was based on the theory developed by Borgand Gall (1983:775), namely the development of 10 steps simplified into 3 steps. Theywere needs analysis (planning), media development and production and evaluation/validation. The data were obtained through observation, interviews, documentationand questionnaires. The quantitative data were then analyzed and described.Based on the data obtained in the research, it can be concluded that AlphabetLetter Creator Module (MoKHA) was suitable for grade 1 students with mild mentalretardation as learning media to recognize alphabets. The students could easily recognizealphabets because this module present simple but interesting materials for thembased on their characteristics.